Consequences of the application of the Financial Operations and Pre- Bankruptcy Settlement Act - Nižić-Peroš, Jadranka (Oeconomica Jadertina, 2020)
The purpose of this paper is to determine the consequences of the application of the Financial Operations and Pre-Bankruptcy Settlement Act (Official Gazette 108/2012, hereinafter: FOPBSA 2012). By taking a specific sample, it will be determined which changes in the business entity’s operations occurred after the pre-bankruptcy settlement proceedings had been instigated, i.e. an attempt will be made to establish whether the liabilities in the pre-bankruptcy settlement proceedings have been settled or written off and whether the business entities continued to operate and unfreeze their accounts or they ceased operations and went belly up. Furthermore, an attempt will be made to determine the methodology and transparency of the actions of the Ministry of Finance and the Tax Administration in making a decision on writing off debts owed to the state. Bankruptcy and prebankruptcy proceedings in the Republic of Croatia clearly show that the issue is complex and that attempts are being made to change and improve it by numerous amendments to the act. This paper analyses specific data on the application of the FOPBSA in 2012. The impact of the application of the act on the state budget is analysed, especially in terms of writing off tax debts. The World Bank’s Doing Business study analyses our position according to the World Bank’s annual report. In order to determine the effect of pre-bankruptcy settlements on the operations of business entities, the aggregate data of the Financial Agency (hereinafter: FINA) deriving from the pre-bankruptcy settlement system as of 1 October 2012 to 11 March 2016 were analysed. Finally, we compared the unexecuted payment orders at the start of the application of the FOPBSA in 2012 and three years after its application. A comparison of the FINA data for the period prior to the entry into force of the FOPBSA in 2012 and the data as per 31 December 2015 shows that at the time when the FOPBSA was in force in 2012, the value of unexecuted payment orders dropped considerably from HRK 43.47 to HRK 24.14 billion, and the number of blocked business entities went down from 72,401 to 41,659. The aim of the research is to assess the impact of the application of FOPBSA 2012 on the continuation of business entities’ operations and, given the sample, to try to draw a conclusion about the actual effect of pre-bankruptcy settlements on the Croatian economy. In one of his quotes, Albert Einstein once said: „The significant problems we face cannot be solved at the same level of thinking we were at when we created them.“